Corpos monumentos: fetichismos visuais em moda nas metrópoles (ModaPalavra e-periódico, 2010)
From a basic product and its advertising in outdoors - in this work, the mark of underwears Mash - the concept of fetish and erotic goes beyond the object in itself. Urban and contemporaries, these propagandas behave in dif erent way in the institution of representations, mainly, because the increasing of the image. Anyway, a gap between the image and its receivers confides, constructing ingenuous perceptions nothing between the look, the looked thing and the desire. To be dressed, therefore, becomes much more that a simple act, since to look at, desire and satisfaction are related constantly in the relations of the people. Thus, the fetished bodies for the advertising also are those that, changed by clothes, constantly relates in the transitory spaces of the cities, that follow under the duo however of desire, however of it repulses, but never in total neutrality, exactly that undressed.
Keywords: Image; Fashion; Outdoors